2022
DOI: 10.3390/cells11050779
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-Related Protein 3 Prevents Diabetic Retinopathy via AMPK-Dependent Stabilization of Blood–Retinal Barrier Tight Junctions

Abstract: Background The impairment of the inner blood–retinal barrier (iBRB) increases the pathological development of diabetic retinopathy (DR), a severe complication in diabetic patients. Identifying approaches to preserving iBRB integrity and function is a significant challenge in DR. C1q/tumor necrosis factor-related protein-3 (CTRP3) is a newly discovered adipokine and a vital biomarker, predicting DR severity. We sought to determine whether and how CTRP3 affects the pathological development of non-proliferative d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Interestingly, CTRP3 was found to promote the secretion of leptin, adiponectin, and visfatin in 3T3-L1 adipocytes [ 227 ]. Furthermore, several studies on different cell types and with animal models demonstrated that CTRP3 may promote AMPK phosphorylation and SIRT1 enhancement [ 228 , 229 , 230 , 231 , 232 ]. To date, little is known about the role of CTRP3 in the development of psoriasis.…”
Section: Other Adipokines and Their Role In Psoriasismentioning
confidence: 99%
“…Interestingly, CTRP3 was found to promote the secretion of leptin, adiponectin, and visfatin in 3T3-L1 adipocytes [ 227 ]. Furthermore, several studies on different cell types and with animal models demonstrated that CTRP3 may promote AMPK phosphorylation and SIRT1 enhancement [ 228 , 229 , 230 , 231 , 232 ]. To date, little is known about the role of CTRP3 in the development of psoriasis.…”
Section: Other Adipokines and Their Role In Psoriasismentioning
confidence: 99%
“…The Nrf2/HO–1 pathway is a target of CTRP3, and suppressor of cytokine signaling 3 is a direct target of miR-455–5p ( Chen et al, 2019 ; Zhang and He, 2019 ). Furthermore, CTRP3 mediates iBRB compatibility and resists vascular permeability induced by DR through the AMPK-dependent occludin/claudin –5 signaling pathway ( Yan et al, 2022 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…The outer layer is primarily composed of retinal pigment epithelial cells and their tight junctions, whereas the inner layer is composed of retinal vascular endothelial cells and their tight junctions. 48 , 49 This barrier prevents substances from leaking out of the blood vessels and controls the entry and exit of immune cells. However, research has demonstrated that various conditions, such as ischemia, hypoxia, inflammation, infection, diabetes, and hypertension, can lead to the detriment of endothelial cells and subsequently disrupt the integrity of the blood-retinal barrie.…”
Section: Discussionmentioning
confidence: 99%